Mechanistic insights and future perspectives of drought stress management in staple crops - Khan, Amir Abdullah; Wang, Yong-Feng; Akbar, Rasheed; Alhoqail, Wardah A. (Frontiers in Plant Science, 2025)
Due to extended periods of below-normal rainfall and rising temperatures, drought is a significant global issue for agricultural productivity. Hydrological, agricultural, and meteorological droughts all pose different problems with regard to the availability of water for important crops, which in turn impacts plant development and yield. Depending on the crop species and stage of maturity, drought stress degrades plant metabolism and physiological processes, resulting in decreased growth and yield losses that can range from 30% to 90%. Acclimatization and adaptation are the two basic techniques that plants use to survive drought. Rapid alterations in physiological processes and chemical composition, including modifications to osmotic pressure, root and leaf size, and antioxidant systems, are all part of acclimatization. Xerophytism and succulence are two characteristics that drought-resistant plants have evolved to assist preserve cellular integrity and water balance in water-limited environments. Even with these tactics, the majority of important crops—such as maize, rice, and wheat—remain extremely vulnerable to drought stress. To lessen the effects of drought, researchers have looked into a number of strategies, including both conventional and cutting-edge methods. Conventional techniques, like the application of plant growth-promoting bacteria (PGPB) and morphological modifications, remain essential for improving drought resilience. Recent breakthroughs have provided innovative alternatives such as nanoparticle (NP) treatments and biochar, which enhance plant resilience. Biochar enhances soil moisture retention and nutrient accessibility, whereas nanoparticles augment water absorption and bolster molecular resilience under stress. Furthermore, microbial inoculants such as plant growth-promoting bacteria (PGPB) enhance nutrient and water absorption, facilitating growth in arid conditions. This review examines the impacts of drought stress on three important staple crops, emphasizing both traditional and novel approaches to lessen the consequences of drought. We highlight how combining insights from ecology, biochemistry, molecular biology, and cutting-edge technologies like biochar and nanoparticles can boost agricultural production and plant resistance in water-scarce environments.